Human cellular differences in cAMP - CREB signaling correlate with light-dependent melatonin suppression and bipolar disorder - Gaspar, Ludmila; van de Werken, Maan; Johansson, Anne-Sophie; Moriggi, Ermanno; Owe-Larsson, Björn; Kocks, Janwillem W. H.; Lundkvist, Gabriella B.; Gordijn, Marijke C. M.; Brown, Steven A. (The European journal of neuroscience, 2014)
Various lines of evidence suggest a mechanistic role for altered cAMP‐CREB (cAMP response element ‐ binding protein) signaling in depressive and affective disorders. However, the establishment and validation of human inter‐individual differences in this and other major signaling pathways has proven difficult. Here, we describe a novel lentiviral methodology to investigate signaling variation over long periods of time directly in human primary fibroblasts. On a cellular level, this method showed surprisingly large inter‐individual differences in three major signaling pathways in human subjects that nevertheless correlated with cellular measures of genome‐wide transcription and drug toxicity. We next validated this method by establishing a likely role for cAMP‐mediated signaling in a human neuroendocrine response to light – the light‐dependent suppression of the circadian hormone melatonin – that shows wide inter‐individual differences of unknown origin in vivo. Finally, we show an overall greater magnitude of cellular CREB signaling in individuals with bipolar disorder, suggesting a possible role for this signaling pathway in susceptibility to mental disease. Overall, our results suggest that genetic differences in major signaling pathways can be reliably detected with sensitive viral‐based reporter profiling, and that these differences can be conserved across tissues and be predictive of physiology and disease susceptibility. Alterations in cAMP/CREB and circadian signaling pathways have been implicated previously in bipolar disorder. In this paper, we use a novel lentiviral methodology to investigate signaling variation over long periods of time directly in human primary fibroblasts taken from bipolar and healthy subjects. Our results show that fibroblast cAMP/CREB signaling amplitude correlates with both light‐dependent melatonin suppression and susceptibility to bipolar disorder. More generally, our data suggest that genetic differences in major signaling pathways can be reliably unearthed by sensitive viral‐based reporter profiling, and that these differences can be conserved across tissues and predictive of neurophysiology and disease susceptibility.